Contaminação microbiológica do ar, detecção de genes de resistência e de síntese de biofilmes em aeronaves comerciais - Nascimento, Jean Phellipe Marques do (2019)
Introduction: Passenger air transport can be pointed out as one of the main means by which the worldwide spread of highly harmful pathogens to human health occurs. Not only that, the problem of bacterial resistance to antibiotics can be amplified for all regions of the world, with air as an extremely effective transmission vehicle. Objectives: a) To monitor the quality of indoor air conditioning in commercial aircraft and to analyze the microbial diversity present; and b) To carry out the tracing of antibiotic resistance genes and biofilm synthesis in the samples collected. Methods: Air-conditioned indoor air collection of commercial aircraft were made during the period when they were on the ground and sampling was done in the cabin of the pilots and in the corridor where they are passengers and crew. For the analyzes, flights with national and international route were selected and these followed the established in Resolution nº 09/2003 of the National Agency of Sanitary Surveillance, which establishes air quality standards in artificially acclimatized environments of public and collective use. Microbiological contamination of the air was evaluated by means of the research of fungal and bacterial aerosols and these were collected through the use of a portable bioaerosol sampler. The captured air was impacted in Petri dishes containing specific media like agar dichloran rose bengal chlorafenicol for fungi and blood agar for bacteria. The collected microorganisms had their identification made based on the macroscopic and microscopic characteristics for the fungi and based on the analysis of the genetic material for bacteria. In addition, screening was done for fungal mycotoxins production and screening of antibiotic resistance genes and for biofilms synthesis in bacteria. Results: There was a considerable diversity of fungi in the samples collected, with the identification of genera with potentially pathogenic species such as Aspergillus, Penicillium, Cladosporium, Fusarium and Paecilomyces. Regarding the production of mycotoxins, only three fungal samples were positive in our screening. Gram negative and positive bacteria with pathogen potential were found, with emphasis on Acinetobacter baumannii, Serratia marcescens, Moraxella osloensis, Streptococcus salivarius and Staphylococcus sp. Screening of antibiotic resistance genes revealed the presence of the following genes: mecA (resistance to methicillin/oxacillin), blaZ (penicillin resistance), ermA, ermB and ermC (cross-resistance to macrolides, lincosamides and streptogramin B). In relation to the biofilms synthesis, only a few isolates of the species Staphylococcus epidermidis exhibited joint detection of icaAD genes, which is directly related to the biofilm formation by these bacteria. The presence of possibly pathogenic microorganisms described here, as well as the report of the occurrence of resistance genes and biofilm production, corroborates the evidence that air is an important medium for the dissemination of virulent microorganisms, posing serious risks to the health of passengers and crew on board. This is the first study in Brazil to evaluate indoor air quality in commercial aircraft. These data point to the need to consider the monitoring and evaluations of factors that may be involved in the presence of fungi and bacteria within the aircraft cabin environment.